Transforming Education - United Nations Executive Office of the Secretary-General (EOSG) (2023)
Building on the Transforming Education Summit and the report of the International Commission on the Futures of Education, the present policy brief examines the current crisis in education in more detail and puts forward a vision and a set of guiding actions for countries and the international community to transform education. The Summit of the Future, to be held in 2024, is an opportunity to agree on multilateral solutions for a better tomorrow, strengthening global governance for both present and future generations. The right to education and lifelong learning is at the very heart of the 2030 Agenda for Sustainable Development because education, knowledge and learning are central to the dignity, growth and development of the individual. For centuries, education has been the great equalizer, a driving force of nation-building, and the engine of social, cultural, economic and technological progress. Today, however, beset by twin crises of equity and relevance, education as we know it is no longer fit for purpose.